Саморегуляція як професійно важлива якість працівника ОВС - Потапова, С. М.; Potapova, S. M.; Землянська, О. В.; Zemlianska, O. V.; ORCID: http://orcid.org/0000-0001-6547-2621 (Право і безпека. - 2015. - № 3 (58). - С. 150–154., 2015)
Висвітлено психологічні аспекти діяльності працівника ОВС на сучасному етапі розвитку суспільства. Підкреслено особливості професійної діяльності працівників у підрозділі правоохоронної системи. Проаналізовано поняття саморегуляції, її зміст та функції. Саморегуляцію розглянуто як професійно важливу якість особистості.

The psychological aspects of the police officers’ activity at the modern stage of the development of the society are highlighted. It is emphasized that the professional activities of the officers in a law enforcement unit has its own characteristics that require not only professional competency, but also some personal qualities, which guarantee the effectiveness of the professional activities. Self-regulation is considered as professionally important quality that guarantees the success of professional activity; in difficult, extreme conditions of performing official tasks it is of great importance. The main functions of self-regulation and self-control within the activity are: 1) address or retention of processes, actions and deeds; 2) switching mental activity; 3) the acceleration or deceleration of mental activity; 4) increase or decrease of the activity; 5) coordination of intentions; 6) control over the activities by the way of comparing its program with the ongoing actions; 7) coordination of actions. In managing the mental states the functions of self-regulation and self-control are as follows: 1) awareness of the content and level of own emotions; 2) self-assessment of physical and mental resources; 3) reflection of the causes of a certain emotional state; 4) overcoming negative state by using willpower; 5) use of measures of psychological discharge. It is concluded that internal reserves of a man that provide him the relative freedom from the circumstances and the possibility of updating even in the most difficult conditions are revealed in the process of self-regulation. An obligatory requirement for effectiveness of the personnel’s actions is its thorough psychological preparation.

Освещены психологические аспекты деятельности работника ОВД на современном этапе развития общества. Подчёркнуты особенности профессиональной деятельности в подразделении правоохранительной системы. Проанализированы понятие саморегуляции, её содержание и функции. Саморегуляция рассмотрена как профессионально важное качество личности.
Potapova, S.M. and Zemlyanskaya, E.V. (2015), “Self-regulation as professionally important quality of a police officer” [“Samorehuliatsiia yak profesiino vazhlyva yakist pratsivnyka OVS”], Pravo i Bezpeka, No. 3, pp. 150–154
Потапова, С. М. Саморегуляція як професійно важлива якість працівника ОВС / С. М. Потапова, О. В. Землянська // Право і безпека. - 2015. - № 3 (58). - С. 150–154.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; особистість; професійно важливі якості; саморегуляція; самоконтроль; саморегуляція діяльності; саморегуляція негативних психічних станів; personality; professional important qualities; self-regulation; self-control; self-regulation of the activity; self-regulation of negative mental states; личность; профессионально важные качества личности; саморегуляция; саморегуляция деятельности; саморегуляция негативных психических состояний; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; органы внутренних дел; працівники ОВС